Comparative evaluation of frictional resistance of silver-coated stainless steel wires with uncoated stainless steel wires: An In vitro study - Priyanka K Shah; Padmaja Sharma; Santosh Kumar Goje (Wolters Kluwer Medknow Publications, 2018)
Background: Silver is known for its antimicrobial activity. Silver coating effectively reduces Lactobacillus acidophilus and Streptococcus mutans count, thus reducing chances of dental plaque and caries. This silver coating may have effect on frictional property of orthodontic wires. Aim: The aim of this study is to evaluate and compare frictional resistance of silver-coated and uncoated stainless steel (SS) wires. Methods: Forty SS wires were divided into four groups of 10 each: Group 1 - 0.017 × 0.025 inch SS wires (silver coated), Group 2 - 0.017 × 0.025 inch SS wires (control), Group 3 - 0.019 × 0.025 inch SS wires (silver coated), and Group 4 - 0.019 × 0.025 inch SS wires (control). Surface modification of wires was carried out by the thermal vacuum evaporation method with silver (10 nm size) using vacuum-coating unit model. The frictional resistances of all forty wires were checked on forty 0.022 × 0.028 inch slot central incisor brackets (SS wires and brackets from American Orthodontics, St Paul, USA) mounted on metal plates using universal testing machine. Results: There was no significant difference found in frictional resistance between silver-coated and uncoated 0.017 × 0.025 inch SS wires group (P = 0.854). Statistically significant reduction in frictional resistance was observed in 0.019 × 0.025 inch coated SS wires in comparison to uncoated wires (P = 0.032). Conclusion: Overall silver coating either did not affect the frictional resistance (0.017 × 0.025 inch SS wires) or reduced it (0.019 × 0.025 inch coated SS wires) compared to uncoated wires. Findings suggest that the use of silver-coated SS wires in routine orthodontic practice can be implemented after further in vivo human clinical trials.